1999
DOI: 10.1001/archfami.8.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ankle Sprain in a General Clinic Population 6 to 18 Months After Medical Evaluation

Abstract: Residual lifestyle-limiting symptoms are common 6 to 18 months after an ankle sprain. Ankle sprains may be more problematic than generally thought, or standard medical treatment may be inadequate. Further studies evaluating treatment regimens are needed to identify effective methods to reduce the long-term functional limitations of ankle sprain in general clinic populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
135
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(138 citation statements)
references
References 25 publications
1
135
0
2
Order By: Relevance
“…Although most athletes return to full activity within 6 weeks of an ankle sprain, a large percentage (4% to 74%) report residual symptoms, including loss of function, repeated injury, and disability. 180,181 Further, many athletes (74%) reported at least 1 residual symptom up to 4 years after injury. 181 Often, an ankle injury is treated as a minor orthopaedic condition; however, in light of these data, clinicians should understand the potential link between ankle injury and CAI.…”
Section: Special Considerations: Caimentioning
confidence: 99%
See 1 more Smart Citation
“…Although most athletes return to full activity within 6 weeks of an ankle sprain, a large percentage (4% to 74%) report residual symptoms, including loss of function, repeated injury, and disability. 180,181 Further, many athletes (74%) reported at least 1 residual symptom up to 4 years after injury. 181 Often, an ankle injury is treated as a minor orthopaedic condition; however, in light of these data, clinicians should understand the potential link between ankle injury and CAI.…”
Section: Special Considerations: Caimentioning
confidence: 99%
“…180,181 Further, many athletes (74%) reported at least 1 residual symptom up to 4 years after injury. 181 Often, an ankle injury is treated as a minor orthopaedic condition; however, in light of these data, clinicians should understand the potential link between ankle injury and CAI. Additionally, repetitive injury and other symptoms associated with CAI may lead to premature osteoarthritis.…”
Section: Special Considerations: Caimentioning
confidence: 99%
“…Entre 40% e 72% das pessoas com entorse de tornozelo experimentam problemas crônicos, incluindo entorses recorrentes e limitação persistente da função (8,9) .…”
Section: Introductionunclassified
“…6 Ankle injuries can result in more long-term lifestyle-limiting disability than commonly perceived. 7,8 Despite the increase in childhood obesity and the high prevalence of trauma in childhood, relatively few studies have been conducted to assess the relationship between the two. A crosssectional survey of 9 to 17 year old children based on self-report showed an association between obesity and the occurrence of injuries, 9 and a chart review of the records of children and adolescents found an association between overweight orthopedic difficulties, including musculoskeletal discomfort and impaired mobility.…”
Section: Introductionmentioning
confidence: 99%